Understanding The Reasons for High Rates of Caesarean Section Deliveries in Telangana, South India: An Explorative Study - Jirra, Karthik; Prasad M, Surya Durga; BR, Shamanna (National Journal of Community Medicine, 2023)
Background: Telangana continues to top the list of the highest number of caesarean section (C-section) deliveries in the country for the financial year 2019-2020. As per NFHS-5 it is about 60.7% deliveries out of the total number of all institutionalized childbirths. This study aims to address the crucial research gap by qualitatively exploring the reasons for the high rates of unnecessary C-section rates in the state of Telangana. Methodology: A purposive sampling was done across the health care facilities and geographies in the State & the districts were selected based on high, medium and low CS rates. A 360-degree stakeholder engagement approach was taken for a qualitative exploration to find out the reasons. Results: Medical, behavioural, cultural, and infrastructure including health system related factors have contributed to the rise of C-sections, particularly unnecessary elective C-sections. Limited trained personnel for doing normal deliveries in the public sector, infrastructure and safety issues for mother and child, and a preference for painless deliveries, and prior CS delivery stood out. Conclusions: As per the study's findings, it can be said that non-medical reasons account for a high percentage of C-sections in Telangana.